Unveiling the psychosocial and academic implications of living with sickle cell disease among undergraduates in a private university in Nigeria - Adeleke, Olumide T.; Folaranmi, Olufemi; Olasinde, Yetunde; Ayuba, Larry; Adeleke, Oludamola V.; Ojo-Rufai, Modupe M.; Agelebe, Efeturi; Adeoye, Oyelola E.; Olabode, Aderemi T.; Ajala, Dolapo E.; Akingbola, Titilola S. (Frontiers in Public Health, 2025)
BackgroundSickle cell disease (SCD), a disease characterized with abnormal red blood cell morphology and is associated with diverse clinical manifestations and contribute to many psychosocial problems like social stigma, strained relationships and reduced self-esteem. SCD is highly prevalent in Sub-Saharan Africa, with Nigeria having the largest burden. This qualitative study is aimed at exploring possible psychosocial and academic challenges associated with sickle cell disease among undergraduates in Nigeria.MethodsFrom September 2023 to February 2024, the authors conducted an exploratory descriptive study using in-depth interviews among 22 undergraduate students with SCD at Bowen University, Osun State, Nigeria, employing an in-depth interviewer guide. Ethical approval was obtained from Bowen University Ethical Review Board prior to the conduct of the study. The data was analyzed using inductive thematic analysis.ResultsSix (6) distinct themes emerged from the research data and each of the themes was linked to the study objectives. Many of the participants expressed disruption of academic activities by frequent SCD crisis. This negatively affected their academic performance, and sometimes led to feelings of frustration. Furthermore, the recurrent battles with pain due to vascular occlusion took a toll on their emotional and psychological health. They also experienced stigmatization and strained interpersonal relationships which negatively influenced their mental well-being. Conversely, some SCD patients enjoy some social support from colleagues and family members which gives hope and succor to them during difficult times.ConclusionThis study reveals that undergraduates with SCD face various academic and psychosocial challenges that affect their overall performance. The findings underscored the need for increased awareness, support, and understanding to better assist undergraduates with SCD in managing their health and academic responsibilities effectively. Considering the chronic nature of SCD and its myriads of psychosocial and academic challenges, measures should be put in place to mitigate the challenges and enable them to live a fulfilling life.